CHALLENGES IN EDUCATIONAL PRACTICE IN BASIC EDUCATION: TEACHERS’ CONCEPTIONS ABOUT THE INCLUSION OF STUDENTS WITH INTELLECTUAL DISABILITIES - Santos, Juanice Pereira; Luz Neto , Daniel Rodrigues Silva; Sousa, Maria Solange Melo de (Revista de Estudos em Educação e Diversidade - REED, 2022)
Current education establishes a paradigm shift to effect the inclusion of special education students in regular education from the perspective of inclusive education. This process is challenging for the school and for teachers who have students with disabilities. The research aimed to investigate the difficulties and challenges faced by teachers in the Final Years of Elementary School in relation to the process of including students with intellectual disabilities. An exploratory qualitative methodology was used with the application of questionnaires and semi-structured interviews. As a theoretical contribution, studies by Mantoan (2003), Pletsch and Glat (2012), Oliveira (2017), Michel (2005), Gil (1999), among others, are highlighted. The results show that, despite the need to include students with intellectual disabilities in regular education, teachers face difficulties, such as the absence of training aimed at inclusion, the inclusion process, knowing students in an integral way, lack of technological resources and the learning of students with intellectual disabilities. Therefore, a dialogue about the current inclusive school is necessary in the search for an instrumented school, a faculty prepared with language, concepts, values and perspective of teaching in the present.